Sensible heat storage in a water tank - Influence of the heat source location and the height of the tank on the temperature distribution - Bello, Benjamin; Leger, Charline (My University, 2014)
Supermarkets need refrigerating devices to keep a cold enough ambiance inside the cabinets. A significant amount of heat is released during the condensation stage of the refrigerating process implemented. Instead of wasting this available energy, it is possible to store it at a certain temperature. The study deals with the sensible heat storage and the storing medium consists of an insulated water tank where the water is heated from 20°C towards 35°C by a heat source representing the heat pumps´ condenser. Regarding sensible heat storage in water tanks, two parameters which can affect the vertical stratification are considered in this report. The purpose is to study how the location of the heat source and the height of the tank influence the temperature distribution. In order to compute the process inside the tank, CFD simulations are run on COMSOL as a combined fluid dynamics and heat transfer model. The study begins with a simplified case where a Dirichlet condition is set on the edges of the tank in order to have a first overview of the phenomenon. Afterwards, more complex studies on the heat source location are carried out to investigate the effect on the temperature distribution when the heat source is immersed. The results show that setting the heating devices on the bottom fosters the temperature homogenization inside the tank and allows having a large amount of hot water available. The configuration where the heat source is on the top of the tank creates a high temperature gradient from the bottom to the top and limits the amount of hot water available. The height of the tank is the last parameter studied and it proves that among several tanks having the same volume, the higher the tank is, the more pronounced the stratification is.
Keywords: Building Futures; Byggnadsteknik; Building Futures; Building engineering